INTERAKSI KELOMPOK PUNK DENGAN NETIZEN (Kajian Fenomenologi Gerakan „Punk Medsos‟ dalam Situs Direktori Konten Punk) - ADITYA FAHMI NURWAHID; Turnomo Rahardjo (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2017)
Punk is a co-cultural group when it comes to dominant cultures which agree on what positivity and negativity are based. In fact, society recognized Punk as a subcultural group concerned on negativity. It can be seen that there are too many cases in violence toward Punk and even Aceh province take action against Punk as they consider it as crum. This condition leads Punk into difficulties when they want to interact with outsiders. This stereotype also develops to be a stigma created by the society that Punk comes along with negativity. Thus, Punk starts the movement through the internet in which they name Punk Directory Sites. It allows Netizen to know more about Punk; how they think and it gives Punk a platform to speak up their ideas. This study used the theories co-cultural theory by Mark Orbe and Computer- Mediated Communication theory by John December. This study also expands the assumptions from Identity Negotiation theory from Stella Ting-Toomey and Self-Disclosure theory by Joseph A. Devito. The interpretative phenomenological analysis used in this study as analytical techniques of the data. The Result of this study show that Punk uses an Accommodation strategy to interact with Netizen. This strategy ranges on the Non-Assertive Accommodation and the Assertive Accommodation. Furthermore, there is a change in Netizen’s viewpoints in which they disagree with the negativity stigma labeled on the Punk. Netizen shows the self-acceptance towards them since Punk attempts to do the identity negotiation in their interaction with Netizen. This identity negotiation results in the feeling of being understood, feeling of being respected, and feeling of being affirmatively valued.